Bio‐Mimicking Brain Vasculature to Investigate the Role of Heterogeneous Shear Stress in Regulating Barrier Integrity. Issue 12 (23rd August 2022) - Mehta, Ami; Desai, Anal; Rudd, David; Siddiqui, Ghizal; Nowell, Cameron J.; Tong, Ziqiu; Creek, Darren J.; Tayalia, Prakriti; Gandhi, Prasanna S.; Voelcker, Nicolas H.
Abstract: A continuous, sealed endothelial membrane is essential for the blood–brain barrier (BBB) to protect neurons from toxins present in systemic circulation. Endothelial cells are critical sensors of the capillary environment, where factors like fluid shear stress (FSS) and systemic signaling molecules activate intracellular pathways that either promote or disrupt the BBB. The brain vasculature exhibits complex heterogeneity across the bed, which is challenging to recapitulate in BBB microfluidic models with fixed dimensions and rectangular cross‐section microchannels. Here, a Cayley‐tree pattern, fabricated using lithography‐less, fluid shaping technique in a modified Hele‐Shaw cell is used to emulate the brain vasculature in a microfluidic chip. This geometry generates an inherent distribution of heterogeneous FSS, due to smooth variations in branch height and width. hCMEC/D3 endothelial cells cultured in the Cayley‐tree designed chip generate a 3D monolayer of brain endothelium with branching hierarchy, enabling the study of the effect of heterogeneous FSS on the brain endothelium. The model is employed to study neuroinflammatory conditions by stimulating the brain endothelium with tumor necrosis factor‐α under heterogeneous FSS conditions. The model has immense potential for studies involving drug transport across the BBB, which can be misrepresented in fixed dimension models. Abstract : Fabrication of a lithography‐less Cayley‐tree pattern to generate a blood‐brain barrier‐on‐a‐chip. The shape of the microchannels in the Cayley‐tree pattern is semi‐elliptical with smooth variation in the height of the microchannels from the parent branch to daughter branches. Heterogeneous fluid shear stress is experienced by the cerebral endothelial cells across the branches of different generations within a single microfluidic device.